2020
DOI: 10.5194/acp-2020-299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of atmospheric transport and biomass burning on the interannual variation in black carbon aerosols over the Tibetan Plateau

et al.

Abstract: Abstract. Atmospheric black carbon (BC) in the Tibetan Plateau (TP) can largely impact regional and global climate. Still, studies on the interannual variation in atmospheric BC over the TP and associated variation in BC sources and controlling factors are rather limited. In this study, we characterize the variations in atmospheric BC over the TP surface layer through analysis of 20-year (1995–2014) simulations from a global chemical transport model, GEOS-Chem. The results show that, of all areas in the TP, su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 79 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…Observations and modeling show an evident interannual variation in aerosols transported from South Asia to the TP during the pre-monsoon season. Previous studies suggested that biomass burning is an important driver of the interannual variations in aerosols over the TP during pre-monsoon 15 . Relatedly, the interannual variation in meteorological fields could also influence the interannual fluctuations in aerosols over the TP [15][16][17] .…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Observations and modeling show an evident interannual variation in aerosols transported from South Asia to the TP during the pre-monsoon season. Previous studies suggested that biomass burning is an important driver of the interannual variations in aerosols over the TP during pre-monsoon 15 . Relatedly, the interannual variation in meteorological fields could also influence the interannual fluctuations in aerosols over the TP [15][16][17] .…”
mentioning
confidence: 98%
“…Previous studies suggested that biomass burning is an important driver of the interannual variations in aerosols over the TP during pre-monsoon 15 . Relatedly, the interannual variation in meteorological fields could also influence the interannual fluctuations in aerosols over the TP [15][16][17] . Focusing on the impacts of winds, large-scale westerlies coupled with valley and glacier winds were found to be essential for aerosol transport toward the TP [18][19][20][21][22][23] .…”
mentioning
confidence: 98%
See 1 more Smart Citation